Technical and Economic Analysis of Use of Post-Treatment Water as a Source of Heat for Heating Water in Breeding Tanks (Agricultural Engineering, 2017)
The paper presents a recommendation on how to use waste heat of post-treatment water in the balneological institute in Lądek Zdrój health resort. This heat may be used in stenothermal fish big scale breeding. The presented innovative solution of a technological breeding line of African sharptooth catfish (Clarias gariepinus) has not been carried out in practice yet and except for ecological values, it may soon bring real profits. The presented calculations show that the analysed technology may bring a real return of the incurred investment expenditures after approx. 6.5 years from the moment the production was launched. The calculated internal return rate is 14.25% and considerably exceeds the border rate (4%). As it was shown, there is an additional possibility of improvement of this profitability through the use of funding as a part of the Operational Programme Fisheries and Sea 2014-2020. Then, at the funding of investment in the amount of 50% of qualified costs IRR will increase to 25.03%. The period of capital return will decrease to approximately 3.5 years.